(untitled) (Revista Apotheke, 2025)
This article reflects on the vibrant life of Casa Minos, an artist’s studio that will celebrate its first anniversary in 2025. The Casa’s goal is to foster a space for living and experimenting, studying, researching, and sharing contemporary art. The ongoing exchanges build affections, understood as the pulse and impulse of knowledge-making in the field of art, in the complex contemporary world. Methodologically, the Casa’s ongoing artistic practice is underpinned by the paradigm of performative research discussed by Brad Haseman. Among the many artistic productions already developed in this space, the text explores the practice of lambe-lambe and the experience of exhibiting the videoperformance “Para o silêncio” (For Silence) at the Treta Festival. From this perspective, Casa Minos is a studio-home that provokes ruptures with Eurocentric ways of existing. Through artistic practice at home, it has been possible to reorganize ways of eating, drinking, sleeping, and, ultimately, living.